Disrupting CD147-RAP2 interaction abrogates erythrocyte invasion by Plasmodium falciparum - Zhang, Meng-Yao (Blood, 2018)
Effective vaccines against malaria caused by Plasmodium falciparum are still lacking, and the molecular mechanism of the host-parasite interaction is not fully understood. Here we demonstrate that the interaction of RAP2, a parasite-secreted rhoptry protein that functions in the parasitophorous vacuole formation stage of the invasion, and CD147 on the host erythrocyte is essential for erythrocyte invasion by P falciparum and is independent from all previously identified interactions involved. Importantly, the blockade of the CD147-RAP2 interaction by HP6H8, a humanized CD147 antibody, completely abolished the parasite invasion with both cure and preventative functions in a humanized mouse model. Together with its long half-life on human red blood cells and its safety profile in cynomolgus monkeys, HP6H8 is the first antibody that offers an advantageous approach by targeting a more conserved late-stage parasite ligand for preventing as well as treating severe malaria.